'And the best essay is…': Extended contact and cross‐group friendships at school. (15th April 2015) - Vezzali, Loris; Stathi, Sofia; Giovannini, Dino; Capozza, Dora; Visintin, Emilio Paolo
Abstract : We conducted one experimental intervention based on extended contact principles aimed at fostering the formation of cross‐group friendships within educational settings. Italian school children took part in a school competition for the best essay on personal experiences of cross‐group friendships with immigrants, to be written in small groups. This manipulation was intended to favour the exchange of personal positive cross‐group experiences, thus capitalizing on the benefits of extended contact. In the control condition, participants wrote an essay on friendship, without reference to cross‐group relations. Results revealed that children who took part in the intervention reported a higher number of outgroup friends 3 months later. This indirect effect was sequentially mediated by pro‐contact ingroup and outgroup norms and by outgroup contact behavioural intentions. This study provides experimental evidence that interventions based on extended contact can foster cross‐group friendship formation. Theoretical and practical implications of the findings are discussed.